Insights from leaders on effectively addressing overweight and obesity in the Thai community - Piyakong, Duangporn; Apiratanawong, Sangduan; Suasing, Chanikan (Universitas Airlangga, 2023)
Introduction: Effective management of health care system at the district level through an important health project can improve health and quality of life of people in the district. Key factors to drive a successful project are important. The purpose of this study was to explore perspectives of leaders managing the health care system at a district level on improving health problems of people in a community through a project according to preventing and solving overweight and obesity issues. Methods: The participants of this qualitative study consisted of nine district health board committees, ten members of the district health system startup team and twenty-four village health system managers. Data was collected by using focus group interviews, observation and documents analysis, also analyzing data by summarizing and categorizing the data of main points. Results: The study results indicated that managing successful health problems at the district level needed: 1) creating clear and equal understanding, 2) having precious community capital and 4) integrating effective incentives for people in the community. Conclusion: The findings of the study can be used as a guideline for managing the health care system in a district level through a project for the development of health issues and the quality of life among people in a community. This successful health system management might be able to help develop the sustainability of public health care at the district level.